Retrospective detection of SARS-CoV-2 in hospitalized patients with influenza-like illness - Xiaoqi Yu; Dong Wei; Yongyan Chen; Donghua Zhang; Xinxin Zhang (Emerging Microbes and Infections)
Since the first report of the coronavirus disease (COVID-19) in late December 2019, the pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has now widely spread to more than 187 countries and regions. However, it is unclear whether there has been cryptic transmission before these early officially confirmed cases, we therefore retrospectively screened for the SARS-CoV-2 RNA in 1271 nasopharyngeal swab samples, as well as the prevalence of IgM, IgG, and total antibodies against SARS-CoV-2 in 357 matched serum samples collected from hospitalized patients with influenza-like illness between 1 December 2018 and 31 March 2020 in Shanghai Ruijin Hospital. The onset date of the earliest COVID-19 case in this study was 25 January 2020. Before this time point, the presence of SARS-CoV-2 was not observed, which limited the possibility that SARS-CoV-2 has already spread among the population before the large-scale outbreak. Additionally, among 6662 patients with influenza-like illness from 1 December 2017 to 31 March 2020, the overall number of patients positive for influenza and other respiratory viruses during the COVID-19 period decreased significantly when compared with that in the same period of the last two years, reflecting that public health interventions can effectively control the spread of common respiratory viruses.